Environmental Pollution - Environmental Pollution (Elsevier, 2026)
Environmental Pollution is an international peer-reviewed journal that publishes high quality research papers and review articles about all aspects of pollution in the environment and its effects on ecosystems and human health. The journal welcomes high-quality process-oriented and hypothesis-driven submissions that report results from original and novel research and contribute new knowledge to help address problems related to environmental pollution at a regional or global scale.
FI 1.5
Q1
Keywords: Earth; Space & Environmental Sciences; Ecotoxicology & Pollution Science; Contaminación; Ecotoxicología; Acuerdos transformativos; Transformative agreements; Contaminantes de interés emergente; Efectos biológicos, ecológicos y en la salud humana; Modelización de los procesos de contaminación.